THE MIRAGE TOOLBOX: AN INTEGRATED ASSESSMENT TOOL FOR TEMPORARY STREAMS. (24th April 2014) - Prat, N.; Gallart, F.; Von Schiller, D.; Polesello, S.; García‐Roger, E. M.; Latron, J.; Rieradevall, M.; Llorens, P.; Barberá, G. G.; Brito, D.; De Girolamo, A. M.; Dieter, D.; et al.
ABSTRACT The assessment of the ecological status of water bodies, as requires by the European Water Framework Directive, can raise a number of problems when applied to temporary streams. These problems are because of the particular physical, chemical and biological conditions resulting from the recurrent cessation of flow or even the complete drying of the stream beds. In such non‐permanent water bodies, the reference quality standards developed for permanent streams may only be applicable under certain circumstances or may not be applicable at all. Work conducted within the collaborative EU‐funded project Mediterranean Intermittent River ManAGEment (MIRAGE) has addressed most of these difficulties and has used diverse approaches to solve them. These approaches have been brought together in the so‐called MIRAGE Toolbox. This toolbox consists of a series of methodologies that are designed to be used in a sequential manner to allow the establishment of the ecological and chemical status of temporary streams and to relate these findings to the hydrological status of the streams. The toolbox is intended to serve the following purposes: (i) the determination of the hydrological regime of the stream; (ii) the design of adequate schedules for biological and chemical sampling according to the aquatic state of the stream; (iii) the fulfillment of criteria for designing reference condition stations; (iv) the analysis of hydrological modifications of the stream regime (with the definition of the hydrological status); and (v) the development of new methods to measure the ecological status (including structural and functional methods) and chemical status when the stream's hydrological conditions are far from those in permanent streams. Copyright © 2014 John Wiley & Sons, Ltd.